Development Entrepreneurship Intention Among Students - Meithiana Indrasari; Raditya Bambang Purnomo; Nur Syamsudin; Eddy Yunus (LPPM of NAROTAMA UNIVERSITY, 2018)
This study aims to describe the actual conditions of student entrepreneurship intentions in the Faculty of Economics and Business of Dr. Soetomo University, to identify the determinants of students' entrepreneurship intent and to formulate methods of approach to improve student entrepreneurship intentions. The background of this research is the low intensi entrepreneurship among students. Intensi entrepreneurship is one of the predisposing factors that determine the ability of seseorag in entrepreneurship. One of the factors that determine how much a person's entrepreneurship intentions to realize entrepreneurial behavior is the academic environment of the campus. This research is a qualitative research with phenomenological approach, where researchers try to explain or reveal the meaning of the concept or the phenomenon of experience based on awareness that occurs in some individuals. In this study the researchers collect, summarize and interpret the data obtained, which then re-processed so that obtained a clear picture, directed and comprehensive of the problem that became the object of research. The phenomenological approach is used to analyze the original data collected from interview questions and dialogue with informants. The structure of experience is illustrated by the researchers' interpretation of the participant description. This article tries to explain how the academic role of campus in cultivating the intention of entrepreneurship to students by using the theory of intention that is the theory of planned behavior